Neuroendocrine carcinoma of gallbladder: a case series and literature review - Wei Liu; Weijie Chen; Jiemin Chen; Tao Hong; Binglu Li; Qiang Qu; Xiaodong He (European Journal of Medical Research, 2019)
Abstract Background Neuroendocrine carcinoma (NEC) of gallbladder is a rare tumor. The clinical manifestation, treatment, and prognosis of gallbladder NEC are rarely reported. Case presentation Eight gallbladder NEC patients were admitted into our hospital. The major complaint was right upper quadrant pain. Two patients underwent a radical resection of gallbladder and liver quadrate lobe. One of them underwent chemotherapies and had no recurrence of NEC during a 25-month followed-up period. The other patient did not undergo chemotherapies, and the NEC recurred in the patient 15 months afterwards. Two patients underwent a radical resection of gallbladder. One of them underwent chemotherapies and had an NEC recurrence 12 months afterwards. The other patient did not undergo chemotherapies and died due to the NEC recurrence 5 months after surgery. Three patients underwent a laparoscopic cholecystectomy and pathologic result showed gallbladder NEC. They did not undergo further treatment and no NEC recurrence was found. One patient underwent tumor biopsy and died due to obstructive jaundice 3 months afterwards. Pathologic results showed that all cases had positive chromogranin A and synaptophysin staining. Conclusions Gallbladder NEC showed no noticeably specific features, and the diagnosis relied on the pathological and immunohistochemistrical results. For T1N0M0 gallbladder NEC, cholecystectomy might be enough. For patients in a late stage, the management of combined therapies might be optimal.